2022
DOI: 10.3390/biom12070892
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Oxidation Promotes Dimerization/Oligomerization of Circadian Protein Period 2

Abstract: The molecular circadian clock is based on a transcriptional/translational feedback loop in which the stability and half-life of circadian proteins is of importance. Cysteine residues of proteins are subject to several redox reactions leading to S-thiolation and disulfide bond formation, altering protein stability and function. In this work, the ability of the circadian protein period 2 (PER2) to undergo oxidation of cysteine thiols was investigated in HEK-293T cells. PER2 includes accessible cysteines suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…One of the mechanisms of molecular circadian clock functioning is based on the half-life of circadian proteins. In their work, Baidanoff et al [ 5 ] investigated the ability of circadian protein period 2 (PER2) to undergo oxidation of thiol groups of cysteine. In this work, the authors showed that cysteine oxidation of PER2 results in the formation of homodimers and multimers in HEK-293T cells.…”
mentioning
confidence: 99%
“…One of the mechanisms of molecular circadian clock functioning is based on the half-life of circadian proteins. In their work, Baidanoff et al [ 5 ] investigated the ability of circadian protein period 2 (PER2) to undergo oxidation of thiol groups of cysteine. In this work, the authors showed that cysteine oxidation of PER2 results in the formation of homodimers and multimers in HEK-293T cells.…”
mentioning
confidence: 99%